Pembuatan Toko Online Produk-Produk Khas di Kawasan Menoreh Kulonprogo - Imam Fahrurrozi; Muhammad Rifqi Al Fauzan; Tika Erna Putri; Rendra Dwi Firmansyah; Ronald Adrian; Atikah Suriani (Jurnal Pengabdian dan Pengembangan Masyarakat, 2018)
One of the activities of dedication to the community of Vocational School UGM aims to create an Online Store of typical products in Menoreh area, Samigaluh District, Kulon Progo Regency. Menoreh is a very potential area not only because of its natural resources, it is proved by the existence of government support through the Ministry of Tourism which establish Menoreh as the National Tourism Strategic Area (KSPN) Borobudur. Menoreh area also save a lot of tourism potential that is still not well developed. Not much information can be obtained from the internet about tours in Menoreh, especially about the original products of Menoreh area such as the chips of the merchant, suroloyo coffee and many other products. So need a special Web-based Online Store to promote these products so as to improve the information and sales of original products of the region. In addition to making the Online Store products typical of the Menorah area, community service activities also provide training for the admin in each village in Menoreh area. As a result the typical products of the Menorah area can be accessed on the URL page: produk.menoreh.org and each village has an admin who is responsible for the promotion of original products from their respective villages.